SUDUT PANDANG HUKUM EKONOMI SYARIAH TERHADAP KETIDAKPASTIAN TRANSAKSI ONLINE TENTANG LARANGAN GHARAR - Zaini Miftah; Fatimatul Jalilah; Mustaqim Makki (KASBANA, 2025)
This study aims to analyze the perspective of Sharia Economic Law on uncertainty in online transactions, particularly those related to the prohibition of gharar (uncertainty or excessive speculation). The phenomenon of online transactions is growing rapidly, but it often contains elements of uncertainty, both in terms of product specifications, payment systems, and delivery mechanisms. This study employs a library research method, analyzing various literary sources such as fiqh books, scientific journals, Islamic Economic Law textbooks, and official fatwas related to online transactions. The results indicate that the prohibition of gharar in online transactions is highly relevant to prevent trading practices that involve uncertainty. From the perspective of Islamic Economic Law, gharar is prohibited because it can harm one party and cause injustice. Therefore, online transactions must adhere to the principles of transparency (al-wuduh), clarity of contracts, and legal certainty, including in terms of product specifications, pricing, and delivery systems. This study recommends strengthening Sharia-based regulations in online transactions to prevent gharar practices and provide legal protection for consumers and businesses. Thus, online transactions can proceed fairly, reliably, and sustainably. Keywords: Gharar, Sharia Economics, Online Transactions. Keywords: Gharar, Sharia Economics, Online Transactions